New Method for Isolation of DNA from River Sediment Microbes of Sungai Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
Extraction of pure genomic DNA from microbes isolated from river sediments often hindered by co-isolated carryovers from the reagents used which reduces the yield and quality of DNA. Existing methods were lengthy, expensive and does not result in high yield of genomic DNA in short time. This study describes a rapid and inexpensive DNA extraction method that involved minimal purification step without phenol or other carcinogenic reagents. The microbial DNA extraction steps also does not require the use of special laboratory equipment. This method uses Cetyltrimethylammonium bromide (CTAB) followed by ethanol based purification steps and within one hour the extraction of microbial DNA could be completed. The extracted genomic DNA from microbes isolated from river sediment of Sungai Kelantan, Malaysia using the method described in this study is of quality suitable for other downstream researches such as metagenomics sequencing.
Keywords: microbes; river sendiment; Sungai Kelantan